The Implementation of One-Stop Integrated Services in Attracting Investment to North Sumatera Province - Anggi Kurniawan Lubis; Erika Revida; Humaizi Humaizi (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aims to analyze the implementation of the One-Stop Integrated Service at the One-Stop Integrated Investment and Licensing Service (DPMPPTSP) of North Sumatera Province and what factors hinder increasing investment. This research method is qualitative with the type of data in the research using primary data through interviews with informants, then secondary data is obtained by conducting an analysis of literature and literature related to research. The analysis technique in this research through reducing data, presenting data and drawing conclusions. The results of this research shows that in order to attract investors to invest in North Sumatera Province, the DPMPPTSP of North Sumatera Province tries to create positive image by removing negative images of poor licensing services. In addition to creating positive image the DPMPPTSP of North Sumatera Province tries to implementing the One-Stop Integrated Service policy which is not yet complete, in the sense that there is still a gap in authority between agencies so that it has not fully met the expectations and satisfaction of users of licensing services and besides that, a complex bureaucracy which makes it difficult for investors to manage business the permits. This causing fluctuate on investment growth. In the context of licensing and non-licensing services the Governor of North Sumatera delegated authority in accordance with the regulation of North Sumatera Governor Number 39 of 2020, delegates its authority to the North Sumatera Province’s DPMPPTSP in particular to provide licensing services and supported community as users of licensing services.